Protective effect of aerobic fitness on the detrimental influence of exhaustive exercise on information processing capacity. (January 2023) - Wang, Chun-Hao; Baumgartner, Nicholas; Nagy, Christian; Fu, Hao-Lun; Yang, Cheng-Ta; Kao, Shih-Chun
Abstract: Although aerobic fitness has been thought to protect against the detrimental cognitive effects following exhaustive exercise, available evidence from studies using traditional mean behavioral measures remain somewhat equivocal. Purpose: This study aimed to reconcile this discrepancy by using a novel theory-driven diagnostic tool, the Systems Factorial Technology (SFT). Methods: Sixty-six healthy young adults aged from 18 to 30 years old with different levels of aerobic fitness ( n  = 33 for the higher-fit and lower-fit groups) completed a go/nogo version of redundant-target task before and after a graded exercise test (GXT) until exhaustion. SFT was used to calculate the resilience capacity, which reflects the information processing capacity underlying inhibitory control. Results: Following the GXT, both higher-fit and lower-fit groups showed faster responses while leaving accuracy unchanged as compared to the performance at the pretest. On the other hand, the resilience capacity decreased for the lower-fit group but was maintained for the higher-fit group. Conclusion: The present findings suggest that aerobic fitness may modulate the individual difference in decisional mechanism following exhaustive exercise. In sum, this study offers an alternative mechanistic explanation regarding cognitive individual differences in response to exhaustive exercise and provides novel insights into the significance of maintaining a state of high physical fitness for those who need to perform cognitively challenging tasks under physically stressful conditions (e.g., elite athletes). Highlights: SFT was employed to examine the fitness effect on cognitive capacity following GXT. Higher aerobic fitness helps maintain cognitive capacity following GXT. Aerobic fitness is vital for optimizing cognition in response to maximal exercise.